2016
DOI: 10.1016/j.str.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Unique Multivalent Readout of Unmodified H3 Tail by Arabidopsis ORC1b BAH-PHD Cassette

Abstract: Summary DNA replication initiation relies on the formation of the Origin Recognition Complex (ORC). The plant ORC subunit 1 (ORC1) protein possesses a conserved N-terminal BAH domain with an embedded plant specific PHD finger, whose function may be potentially regulated by an epigenetic mechanism. Here, we report structural and biochemical studies on the Arabidopsis thaliana ORC1b BAH-PHD cassette which specifically recognizes the unmodified H3 tail. The crystal structure of ORC1b BAH-PHD cassette in complex w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Both readers create the binding site and surround the same region of the peptide. The extensive set of hydrogen bonds formed between BAH–PHD and the side chains of the histone R2, T3, and K4 residues suggests that modification of these residues would prevent binding, and this has been confirmed experimentally 47 .…”
Section: Crosstalk Of Paired Readersmentioning
confidence: 69%
See 1 more Smart Citation
“…Both readers create the binding site and surround the same region of the peptide. The extensive set of hydrogen bonds formed between BAH–PHD and the side chains of the histone R2, T3, and K4 residues suggests that modification of these residues would prevent binding, and this has been confirmed experimentally 47 .…”
Section: Crosstalk Of Paired Readersmentioning
confidence: 69%
“…The ORC1b PHD finger sequence is embedded in the sequence of BAH, and this unique assembly of readers recognizes unmodified histone H3 tail (residues 1–8) 47 . In the BAH–PHD–H3 complex, the peptide adopts an extended conformation and occupies a long groove at the interface of the readers (Fig.…”
Section: Crosstalk Of Paired Readersmentioning
confidence: 99%
“…Maize ZMET2, mouse ORC1, and Arabidopsis ORC1b utilize their BAH domains to recognize H3K9me2, H4K20me2, and unmodified H3, respectively (Supplementary Fig. 5a–c ) 29 , 47 , 48 . Here, we revealed that SHL BAH is engaged in H3K27me3 recognition, similar to the BAH domain of BAHD1 protein 49 .…”
Section: Discussionmentioning
confidence: 99%
“…The Arabidopsis ORC1b BAH domain together with a PHD finger combinatorially recognize unmodified H3 using a different interface (Supplementary Fig. 5c ) 47 , suggesting a distinct histone binding interface other than the aromatic cage.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is likely that the Tudor-SN interface recognition mode is conserved among at least a subgroup of eTudor domain proteins. Notably, the interface of BAH-PHD or Ankyrin-Chromo has also been reported to recognize unmodified ligands (24,25). For germline-specific TDRD family proteins, methylation-independent and methylation-dependent eTudor-PIWI interactions may act in a cooperative temporal-spatial fashion and together facilitate the formation of the piRNA machinery and optimal biogenesis of piRNAs.…”
Section: Significance Of Arginine Methylation-independent Tdrd2-piwil1mentioning
confidence: 99%